2019
DOI: 10.1155/2019/3290958
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Vertical Dynamic Responses of Three Types of Elevated Railway Tracks Subjected to a Moving Train

Abstract: A theoretical model incorporating the moving train, the railway track, and the elevated viaduct is established and then solved using periodic theory in this paper. The vertical wheel/rail forces and the dynamic responses of track and viaduct girder are obtained and compared for three different types of tracks, i.e., the double-block ballastless track, the rubber-pad floating slab track, and the steel-spring floating slab track. It is observed that the rubber-pad and steel-spring floating slab tracks can reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In addition, due to time and space constraints in the tunnel, it is greatly difficult to perform timely maintenance on the track structure. For this reason, a new type of prefabricated rubber floating slab track structure (Liu, 2012;Shi et al, 2019) is proposed, which has an improved structure and uses the stiffness and damping characteristics of the rubber cushion to achieve vibration dissipation and attenuation. Yuze et al (2013) CAO et al (2013 concluded that there is a need for a reasonable thickness of the monolithic track bed by analyzing the natural frequency, mechanical response, and vibration damping performance; From the foregoing, it can be seen that many scholars have conducted detailed studies on the mechanical properties of the rubber damping ballastless track structure, but most of them focused their attention on the cast-in-place ballastless track.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, due to time and space constraints in the tunnel, it is greatly difficult to perform timely maintenance on the track structure. For this reason, a new type of prefabricated rubber floating slab track structure (Liu, 2012;Shi et al, 2019) is proposed, which has an improved structure and uses the stiffness and damping characteristics of the rubber cushion to achieve vibration dissipation and attenuation. Yuze et al (2013) CAO et al (2013 concluded that there is a need for a reasonable thickness of the monolithic track bed by analyzing the natural frequency, mechanical response, and vibration damping performance; From the foregoing, it can be seen that many scholars have conducted detailed studies on the mechanical properties of the rubber damping ballastless track structure, but most of them focused their attention on the cast-in-place ballastless track.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, due to time and space constraints in the tunnel, it is greatly difficult to perform timely maintenance on the track structure. For this reason, a new type of prefabricated rubber floating slab track structure (Liu, 2012; Shi et al, 2019) is proposed, which has an improved structure and uses the stiffness and damping characteristics of the rubber cushion to achieve vibration dissipation and attenuation. Yuze et al (2013) CAO et al (2013) concluded that there is a need for a reasonable thickness of the monolithic track bed by analyzing the natural frequency, mechanical response, and vibration damping performance; Hong et al (2021) ZHOU et al (2021) analyzed the dynamic response of passive rubber damping track and frame-type slab track with resonance masses; Qing et al (2021) FAN et al (2021) studied the vehicle-structure dynamic performance when passing straight and curved trapezoidal sleeper tracks; Ren (2019) calculated the deformation and moment of the track slab under different working conditions and provided guiding suggestions for guiding the track structure design; Peng and Tao (2018) CHEN et al (2018) studied the vibration characteristics of the track system, and proposed stiffness of the rubber with the best damping performance; Chen et al (2019) conducted dynamic research and comparative analysis on the geotextile of the prefabricated slab ballastless track structure; Zhong et al (2021) CHEN et al (2013) proposed a new type of movable frame slab ballastless track and analyzed the structural dynamic performance; Zhonghua (2013) analyzed the influence of the slab size and the stiffness of the rubber cushion on the structural mechanics; Peng et al (2017) YU et al (2017) conducted modal and resonance analyses on track slab structures under different rubber cushion stiffnesses; Yanglong (2014) ZHONG (2014) pointed out that the thickness of the track slab and the stiffness of the rubber cushion have significant effects on the vibration of the track structure; Jin et al (2016) discussed the impact of the full-paved, strip-paved, and spot-paved rubber cushion on the vibration damping performance of the track structure.…”
Section: Introductionmentioning
confidence: 99%